The Inferior Nuchal Line as a Simple Landmark for Identifying the Vertebral Artery During the Retrosigmoid Approach. Issue 3 (19th June 2019) - Tayebi Meybodi, Ali; Zhao, Xiaochun; Borba Moreira, Leandro; Lawton, Michael T; Lang, Michael J; Labib, Mohamed; Preul, Mark C
Abstract: BACKGROUND: The V3 segment of the vertebral artery (V3 -VA) is at risk during various approaches to the craniovertebral junction. Several landmarks have been defined to identify V3 -VA, but these landmarks are not routinely exposed during a retrosigmoid (RS) approach, where musculocutaneous dissection inferiorly towards the foramen magnum can threaten this arterial segment. OBJECTIVE: To find a landmark that will identify the V3 -VA during the RS approach, and analyze the inferior nuchal line (INL) as this novel landmark. METHODS: The anatomic relationships between the INL and the V3 -VA were assessed in 7 cadaveric heads through RS exposure in the lateral position. RESULTS: The INL is an L-shaped bony ridge with horizontal (medial) and vertical (lateral) arms, with the vertical arm being more conspicuous in all specimens (INLV ). The mean depths of the V3 -VA relative to the medial and lateral ends of the INLV were (mean ± standard deviation) 24.9 ± 7.1 mm, and 8.3 ± 3.2 mm, respectively. In all specimens, the V3 -VA was located inferior and anterior to the INLV . CONCLUSION: The INL provides an important landmark during RS approach that can protect the V3 -VA from inadvertent injury or identify it for use in an interpositional bypass. The INLV identifies the region of the suboccipital triangle where the V3 -VA is embedded. INLV is routinely seen during the RS approach, making it more relevant than other classic landmarks such as the transverse process of C1, C1 posterior arch, and the atlantomastoid line that are not exposed during the RS approach.